8-Oxoguanine DNA glycosylase1–driven DNA repair—A paradoxical role in lung aging. (January 2017) - German, Peter; Saenz, David; Szaniszlo, Peter; Aguilera-Aguirre, Leopoldo; Pan, Lang; Hegde, Muralidhar L.; Bacsi, Attila; Hajas, Gyorgy; Radak, Zsolt; Ba, Xueqing; Mitra, Sankar; Papaconstantinou, John; et al.
Graphical abstract: Visual illustration for role of OGG1-BER in senescence/aging processes. In this model OGG1-BER and generation of OGG18-oxoG complex (a guanine nucleotide exchange factor) increases levels of activated small GTPases. Downstream from small GTPases transcription factors (TFs) are activated leading to differential expression of mediators and "fueling" senescence/aging processes as shown by gene ontology enrichment and visualization analysis. P values of biological processes are depicted by colors. Highlights: Aging is genetically regulated, and is accelerated by stress from environment. Generation of genomic 8-oxoguanine and aging are parallel processes. OGG1-BER of 8-oxoG, fuels activation of small GTPases and gene expression. GO analyses of OGG1-BER-associated gene expression are relevant to senescence-aging. Pharmaceutical modulation of guanine oxidation in DNA should decelerate aging processes. Abstract: Age-associated changes in lung structure and function are some of the most important predictors of overall health, cognitive activities and longevity. Common to all aging cells is an increase in oxidatively modified DNA bases, primarily 8-oxo-7, 8-dihydroguanine (8-oxoG). It is repaired via DNA base excision repair pathway driven by 8-oxoguanine DNA glycosylase-1 (OGG1-BER), whose role in aging has been the focus of many studies. This study hypothesizes that signaling and consequent gene expression during cellular response to OGG1-BER "wires" senescence/aging processes. To test OGG1-BER was mimicked by repeatedly exposing diploid lung fibroblasts cells and airways of mice to 8-oxoG base. Results showed that repeated exposures led to G1 cell cycle arrest and pre-matured senescence of cultured cells in which over 1000 genes were differentially expressed −86% of them been identical to those in naturally senesced cells. Gene ontology analysis of gene expression displayed biological processes driven by small GTPases, phosphoinositide 3-kinase and mitogen activated kinase cascades both in cultured cells and lungs. These results together, points to a new paradigm about the role of DNA damage and repair by OGG1 in aging and age-associated disease processes.